Potential role for all-trans retinoic acid in nonpromyelocytic acute myeloid leukemia. (December 2016) - Ma, Hayley S; Robinson, Tara M; Small, Donald
All- trans retinoic acid (ATRA) has been very successful in the subtype of acute myelogenous leukemia known as acute promyelocytic leukemia due to targeted reactivation of retinoic acid signaling. There has been great interest in applying this form of differentiation therapy to other cancers, and numerous clinical trials have been initiated. However, ATRA as monotherapy has thus far shown little benefit in nonacute promyelocytic leukemia acute myelogenous leukemia. Here, we review the literature on the use of ATRA in combination with chemotherapy, epigenetic modifying agents and targeted therapy, highlighting specific patient populations where the addition of ATRA to existing therapies may provide benefit. Furthermore, we discuss the impact of recent whole genome sequencing efforts in leading the design of rational combinatorial approaches.